The Value of Sportsmanship in the Traditional Game of Bob Wrestling of the Marind Tribe - Chandra Novian Kaize; Muhammad Ishaq Gery; Doby Putro Parlindungan; Taufik Yudi Mulyanto; Galang Pakarti Mahardika (Indonesian Values and Character Education Journal, 2025)
This research addresses the issue of sportsmanship values in the traditional game of Bob Wrestling from the Marind Tribe, which often lacks adherence to fair play principles. Utilizing a quantitative descriptive design, the study analyzes participant attitudes towards sportsmanship within this cultural context. Data collection instruments included structured questionnaires and documentation, focusing on indicators such as commitment to sport, social conventions, compliance with regulations, and positive attitudes. Findings indicate that the sportsmanship value of Bob Wrestling falls within a medium to high category, with 48% of respondents classified as medium, 30% as high, and 12% as very high. This suggests a significant link between totemism and sportsmanship, highlighting the protective role of cultural values in fostering fair competition. In conclusion, the research emphasizes the importance of integrating local cultural values into sports education to enhance sportsmanship among participants, contributing to the preservation of traditional games and promoting positive attitudes in competitive settings.